Isokinetic Exercises in Quadriceps Strength and Endurance Recovery After Anterior Cruciate Ligament Reconstruction - Dragičević-Cvjetković, Dragana; Erceg-Rukavina, Tatjana; Jovičić, Željko (Scripta Medica, 2022)
Background/Aim: Muscle strength and endurance recovery of the quadriceps after anterior cruciate ligament reconstruction is necessary for normal knee function. In addition to the use of the isokinetic dynamometer for diagnostic purposes, its possible therapeutic effect is also important, ie targeted correction of the measured muscle deficit. This work was aimed to examine the level of quadriceps strength and endurance recovery 6 months after the anterior cruciate ligament reconstruction in patients who performed isokinetic training and to determine whether it is a superior therapeutic intervention compared to isodynamic training. Methods: A total of 70 patients of both sexes were monitored in a prospective clinical study. Three months postoperatively, all patients had quadriceps torque measured to body weight on an isokinetic dynamometer at angular speeds of 60 and 180 °/s. Patients were divided into two groups according to the type of applied rehabilitation protocol. Group A patients (n = 35) underwent a rehabilitation program 5 times a week using an individual kinesitherapy program (isometric and isotonic exercises for quadriceps and hamstrings) and neuromuscular electrostimulation of the quadriceps. In addition patients from group B (n = 35) were included in targeted isokinetic exercises for the quadriceps. Control isokinetic testing was performed 6 months after surgery. The comparison of the effect of the applied therapeutic procedures in groups A and B was performed with the Student t-test (p < 0.05). Results: An average age of patients was 27.29 ± 5.94 years. In patients in group B, statistically significantly higher values of the peak torque to body weight were measured at angular velocities of 60 and 180 °/s for the quadriceps of the operated knee 6 months after reconstruction of the anterior cruciate ligament with hamstring tendons (p < 0.05). Conclusion: Isokinetic training achieved significantly better quadriceps strength and endurance in patients 6 months after anterior cruciate ligament reconstruction with hamstring tendons compared to dynamic exercises.